Advances in the pharmacological treatment of hepatic alveolar echinococcosis: From laboratory to clinic - Xu, Xiaolei; Qian, Xinye; Gao, Cancan; Pang, Yuan; Zhou, Hu; Zhu, Lizhen; Wang, Zhan; Pang, Mingquan; Wu, Defang; Yu, Wenhao; Kong, Fanyu; Shi, Dalin; et al. (Frontiers in Microbiology, 2022)
Hepatic alveolar echinococcosis (HAE) is a zoonotic parasitic disease caused by the larvae of Echinococcus multilocularis. Because of its characteristics of diffuse infiltration and growth similar to tumors, the disability rate and mortality rate are high among patients. Although surgery (including hepatectomy, liver transplantation, autologous liver transplantation) is the first choice for the treatment of hepatic alveolar echinococcosis in clinic, drug treatment still plays an important and irreplaceable role in patients with end-stage echinococcosis, including patients with multiple organ metastasis, patients with inferior vena cava invasion or patients with surgical contraindications, etc. However, Albendazole is the only recommended clinical drug which could exhibit a parasitostatic rather than a parasitocidal effect. Novel drugs are needed but few investment was made in the field because the rarity of the cases. Drug repurposing might be a solution. In this review, FDA approved drugs have a potential curative effect on hepatic alveolar echinococcosis in animal models are summarized. Further, nano drug delivery system boosting the therapeutic effect on hepatic alveolar echinococcosis are also reviewed. Taked together, these might contribute to the development of novel strategy for advanced hepatic alveolar echinococcosis.